HEALTH EDUCATION OF NO SMOKING BEHAVIOR IN ADOLESCENTS WITH A SOCIAL COGNITIVE THEORY (SCT) APPROACH - Riyadi, Sujono; Ru’iya, Sutipyo (The Indonesian Journal of Public Health, 2025)
Introduction: Smoking behavior is an action that can harm the smoker himself and can even harm others (passive smokers). Someone who is exposed to cigarettes for a long time will result in health problems and disease, Out of 800 junior high school youth in Kulon Progo, 5.3% are smokers. Aims: To determine the factors that influence directly or indirectly on the behavior of not smoking in adolescents. Methods: This case-control study was conducted in Kulon Progo Regency, Yogyakarta Special Region Province, Indonesia. The samples were 400 teenagers, 200 teenagers who smoked (cases) and 200 other teens who didn't smoke (controls). Data were collected using a questionnaire filled out by teenagers who are still active in school in junior high and high school. There are six variables studied including knowledge, media exposure, non-smoking attitudes, self-efficacy, non-smoking intentions and non-smoking behavior. Data were analyzed multivariately using STATA 13 Result:   There are two variables (intention and self-efficacy) that have a direct influence on adolescents' non-smoking behavior, while the other three variables (knowledge, media exposure and attitude) have an indirect influence on adolescents' non-smoking behavior. Conclusion: Intention variable has the biggest contribution in influencing adolescent behavior not to smoke.